PENINGKATAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN CANVA DI KELAS V SDN 03 BANDAR BUAT - Erison, Zanzabilla; Waldi, Atri; Rahmi, Gita; Anita, Yesi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aimed to describe the improvement of students’ learning This classroom action research aimed to describe the improvement of students’ learning outcomes in Pancasila Education using the Contextual Teaching and Learning (CTL) model assisted by Canva in Grade V at SDN 03 Bandar Buat. The research was motivated by students’ low participation in asking and answering questions and expressing opinions, difficulties in relating learning materials to everyday life, teacher-centered learning, and the suboptimal use of instructional media. The initial condition showed that only 7 of 26 students (26.92%) achieved the Learning Achievement Criteria (KKTP) of 80, with a class average score of 59.23. The research used qualitative and quantitative approaches with Classroom Action Research (CAR), conducted in two cycles and three meetings. Each cycle consisted of planning, implementation, observation, and reflection. The subjects were 26 fifth-grade students in the first semester of the 2026/2027 academic year. Data were collected through observation, tests, and documentation, and analyzed using percentages, mean scores, and learning mastery. The results showed improvements in the learning process and outcomes. The lesson-plan assessment increased from 89.28% to 96.42%, teacher activity from 84.72% to 91.67%, and student activity from 81.90% to 94.40%. Learning outcomes in attitude increased from 76.02% to 85.65%, knowledge from 65.39% to 88.46%, and skills from 72.84% to 88.46%. Thus, the implementation of CTL assisted by Canva can improve the learning process and students’ learning outcomes in Pancasila Education.